The association between ownership of common household devices and obesity and diabetes in high, middle and low income countries - Lear, Scott A.; Teo, Koon; Gasevic, Danijela; Zhang, Xiaohe; Poirier, Paul P.; Rangarajan, Sumathy; Seron, Pamela; Kelishadi, Roya; Tamil, Azmi Mohd; Kruger, Annamarie; Iqbal, Romaina; Swidan, Hani; et al. (Canadian Medical Association journal (CMAJ), 2014)
Household devices (e.g., television, car, computer) are common in high income countries, and their use has been linked to obesity and type 2 diabetes mellitus. We hypothesized that device ownership is associated with obesity and diabetes and that these effects are explained through reduced physical activity, increased sitting time and increased energy intake. We performed a cross-sectional analysis using data from the Prospective Urban Rural Epidemiology study involving 153,996 adults from high, upper-middle, lower-middle and low income countries. We used multilevel regression models to account for clustering at the community and country levels. Ownership of a household device increased from low to high income countries (4% to 83% for all 3 devices) and was associated with decreased physical activity and increased sitting, dietary energy intake, body mass index and waist circumference. There was an increased odds of obesity and diabetes with the ownership of any 1 household device compared to no device ownership (obesity: odds ratio [OR] 1.43, 95% confidence interval [CI] 1.32-1.55; diabetes: OR 1.38, 95% CI 1.28-1.50). Ownership of a second device increased the odds further but ownership of a third device did not. Subsequent adjustment for lifestyle factors modestly attenuated these associations. Of the 3 devices, ownership of a television had the strongest association with obesity (OR 1.39, 95% CI 1.29-1.49) and diabetes (OR 1.33, 95% CI 1.23-1.44). When stratified by country income level, the odds of obesity and diabetes when owning all 3 devices was greatest in low income countries (obesity: OR 3.15, 95% CI 2.33-4.25; diabetes: OR 1.97, 95% CI 1.53-2.53) and decreased through country income levels such that we did not detect an association in high income countries. The ownership of household devices increased the likelihood of obesity and diabetes, and this was mediated in part by effects on physical activity, sitting time and dietary energy intake. With increasing ownership of household devices in developing countries, societal interventions are needed to mitigate their effects on poor health.